2020
DOI: 10.1016/j.ijbiomac.2020.03.119
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antipsychotic clozapine binds fibrinogen and affects fibrin formation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Clozapine has also been found to increase platelet adhesion and aggregation and reduce activated partial thromboplastin time (aPTT), 19 which can lead to the development of VTE. A recent in vitro study revealed that in a dose‐dependent manner, clozapine affects fibrin formation by reducing coagulation speed and fibrin fiber thickness, leading to fibrinogen acquiring increased thrombogenic properties 20 . Treatment with clozapine for a duration longer than 2½ years can lead to elevated serum concentrations of IgM antiphospholipid antibodies, which are, although rarely, associated with arterial and venous thrombosis 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clozapine has also been found to increase platelet adhesion and aggregation and reduce activated partial thromboplastin time (aPTT), 19 which can lead to the development of VTE. A recent in vitro study revealed that in a dose‐dependent manner, clozapine affects fibrin formation by reducing coagulation speed and fibrin fiber thickness, leading to fibrinogen acquiring increased thrombogenic properties 20 . Treatment with clozapine for a duration longer than 2½ years can lead to elevated serum concentrations of IgM antiphospholipid antibodies, which are, although rarely, associated with arterial and venous thrombosis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vitro study revealed that in a dose-dependent manner, clozapine affects fibrin formation by reducing coagulation speed and fibrin fiber thickness, leading to fibrinogen acquiring increased thrombogenic properties. 20 Treatment with clozapine for a duration longer than 2½ years can lead to elevated serum concentrations of IgM antiphospholipid antibodies, which are, although rarely, associated with arterial and venous thrombosis. 21 Our patient had commenced clozapine only 14 days prior, and while anti-phospholipid antibody levels were not evaluated in our patient, serum analysis showed a normal APTT (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent in vitro study revealed that clozapine enhances the risk of developing thrombosis in patients on CLZ, by reducing coagulation time and fibrin fibers' thickness, developing a thrombogenic pattern in a dose-dependent manner [85].…”
Section: Clozapine Risk Of Pulmonary Embolism and Pneumoniamentioning
confidence: 99%
“…Another hematological side effect might be at the root of the venous thromboembolism in the patients treated with clozapine -the increases in adhesion and aggregation of blood platelets [78]. A recent in vitro study revealed that clozapine binding affected fibrin formation by reducing coagulation speed and thickness of fibrin fibers by fibrinogen developing thrombogenic characteristics, dose-dependent, increasing the risk for development thrombosis in patients on clozapine treatment [79]. Patients diagnosed with schizophrenia are at higher risk of obesity and cardiovascular diseases; this observation being another pathophysiological explanation of the increased risk of pulmonary embolism [80] but also of aspiration pneumonia [81].…”
Section: Clozapine Risk Of Pulmonary Embolism and Pneumoniamentioning
confidence: 99%